Four new species and new records of Platygastrinae (Hymenoptera: Platygastridae) from Iran - Asadi-Farfar, Maryam; Karimpour, Younes; Lotfalizadeh, Hossein; Buhl, Peter Neerup (European Journal of Taxonomy, 2021)
The following four species new to science are described: Platygaster azarbaijanica Buhl & Asadi sp. nov., Platygaster lotfalizadehi Buhl & Asadi sp. nov., Platygaster karimpouri Asadi & Buhl sp. nov. and Synopeas calecai Buhl & Asadi sp. nov. Diagnostic characters are discussed, and figures are provided to distinguish the new species. In addition, ten species of Platygastrinae Howard, 1892 belonging to the genera Platygaster Latreille, 1809, Synopeas Förster, 1856 and Leptacis Förster, 1856 are reported as new records for the fauna of Iran. Four species of Platygaster and one species of Synopeas are recorded as ʻconferʼ.